Digital Transformation as a Driver for Improving the Effectiveness of Integrated Social Services - Aghajanyan, Martin («ԱՐՑԱԽ» հրատ.)
The purpose of this article is to explore the impact of digitalization on social protection systems, with a focus on how it improves service delivery mechanisms, efficiency, and accessibility. While the benefits of digital transformation are clear, the full digitalization of social services presents challenges for developing countries, and existing industry research insufficiently clarifies the intricate consequences of this phenomenon. This article seeks to address this gap by examining the benefits of digitalization, such as enhanced efficiency and accessibility, while also analyzing challenges, including the risks of digital exclusion and data privacy violations. The research employed analytical, synthetic, inductive, and deductive methods. The article elucidates the advantages and obstacles of delivering digital services, specifically emphasizing the unified social service of the Republic of Armenia. The article's novelty stems from its holistic approach, integrating global trends in digital transformation with the digitalization necessities of the USS. It underscores the determinants of successful digitalization, including legal reforms, enhanced digital literacy, and upgraded infrastructure, which should influence decision-makers and implementers. Տվյալ հոդվածի նպատակն է ուսումնասիրել թվայնացման ազդեցությունը սոցիալական պաշտպանության համակարգերի վրա՝ ուշադրության դիտակետում ունենալով ծառայությունների տրամադրման կառուցակարգերի, արդյունավետության և մատչելիության բարելավման գործընթացներում թվայնացման դերը: Չնայած թվային փոխակերպման հստակ առավելություններին՝ սոցիալական ծառայությունների ամբողջական թվայնացումը դեռևս մարտահրավեր է զարգացող երկրների համար, իսկ առկա ոլորտային ուսումնասիրությունները ամբողջապես չեն բացահայտում այդ երևույթի բազմակողմանի ազդեցությունները: Այս հոդվածն անդրադառնում է այդ բացին՝ ընդգծելով և՛ առավելությունները, ինչպիսիք են բարձրացված արդյունավետությունն ու հասանելիությունը, և՛ մարտահրավերները՝ ներառյալ՝ թվային բացառման և տվյալների պաշտպանության խախտումների վտանգները: Цель данной статьи - изучить влияние цифровизации на системы социальной защиты, акцентируя то, как она улучшает механизмы предоставления услуг, повышает их эффективность и доступность. Несмотря на явные преимущества цифровой трансформации, полная цифровизация социальных услуг по-прежнему является проблемой для развивающихся стран, при этом существующие отраслевые исследования не раскрывают в полной мере многогранные эффекты этого явления. В данной статье рассматривается этот пробел, подчеркиваются как преимущества, такие как повышение эффективности и доступности, так и проблемы, включая риски цифрового исключения и нарушений защиты данных. В ходе исследования использовались методы анализа, синтеза, индукции и дедукции. С использованием данных методов в статье освещаются преимущества и проблемы предоставления цифровых услуг, уделяется особое внимание единой социальной службе РА.
Keywords: Political science; International relationships